Pathophysiology for the Pediatric Critical Care Fellow: Three Representative Simulation Cases - Candace Mannarino; Erin Bradley; Amanda Puro; Deborah Sung; Katie Wolfe (Association of American Medical Colleges, 2020)
Introduction During the course of fellowship training, pediatric critical care fellows are expected to develop a broad and in-depth understanding of the pathophysiology of multiple disease processes. The simulation-based pediatric critical care pathophysiology curriculum we present uses scenarios created by pediatric critical care fellows to teach complex pathophysiology. Methods Each of the three representative cases presented covered a specific pathophysiologic process and required participants to acutely manage (1) an 18-year-old patient with altered mental status in the setting of hepatic encephalopathy; (2) an 8-year-old patient with sepsis, coagulopathy, and acute kidney injury; or (3) a 12-year-old patient with status epilepticus. Each case could be conducted in a simulation suite or an acute care unit bed. We assessed learners' knowledge and attitudes at the end of these simulations with a structured debriefing session and via completion of an evaluation form. The simulations were then followed by a 30-minute interactive didactic session on the topic. Results Each scenario had six fellow participants who completed evaluations. After completing each of the three case scenarios presented, the majority of participating pediatric critical care fellows indicated that the content was relevant and sufficiently challenging. They also indicated that these simulation scenarios would improve their clinical practice. Discussion This fellow-developed simulation curriculum is novel, highlighting the relevance for critical care fellows' understanding of realistic clinical scenarios while promoting advanced management skills with a pathophysiology focus.